Assessment of the impact of pH of wound fluid on the associated microbial distribution in the cases of infected diabetic foot ulcer - Aradhana Singh; Shailendra Rai; Arvind Pratap; Tuhina Banerjee; Mumtaz Ahmed Ansari; Somprakas Basu; Vijay Kumar Shukla (Journal of Family Medicine and Primary Care)
Background: Diabetic foot ulcers (DFUs) are the most common complication associated with diabetes mellitus and foremost cause of lower extremity amputations with over a million individuals undergoing amputations per year. Purpose: This descriptive cross-sectional study was carried out to determine the association between the pH of the wound fluid in the infected DFUs with the type of associated microflora. Material and Methods: One hundred patients suffering from DFUs were included in the present study. The pH measurement of the wound fluid of DFUs patient along with aerobic/facultative anaerobic microflora through quantitative culture technique and anaerobic microflora through molecular techniques was assessed. The demographic data (age, gender), type of microflora, and chronicity of the DFU were statistically analysed with the pH of the wound fluid. Results: The majority of the DFUs were polymicrobial in nature. Peptococcus (24.8%) was the most common microorganism identified, followed by Escherichia coli (11.8%). No association was found between the associated microflora and the pH of the wounds. The chronic ulcers (≥12 months) were found to be significantly associated with the alkaline pH (P = 0.013). Conclusion: The pH of the wound is not a significant indicator for the type of associated microflora in the cases of infected DFUs based on single sampling at presentation.